2007
DOI: 10.1542/peds.2006-2089e
|View full text |Cite
|
Sign up to set email alerts
|

Children's Mental Health and Family Functioning in Rhode Island

Abstract: OBJECTIVES. Our objectives were to (a) estimate the prevalence of children's mental health problems, (b) assess family functioning, and (c) investigate the relationship between children's mental health and family functioning in Rhode Island. METHODS. From the 2003 National Survey of Children's Health, Rhode Island data for children 6 to 17 years of age were used for the analyses (N = 1326). Two aspects of family functioning measures, parental stress and parental involvement, were constructed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 9 publications
5
34
0
2
Order By: Relevance
“…Kim et al recently reported one in five (19%) communitydwelling children and adolescents aged 6-17 years to have mental health problems [25]. The similarity of these two figures supports our finding that mental disorders are nearly four times more common in currently self-cutting adolescents than among other adolescents.…”
Section: Discussionsupporting
confidence: 90%
“…Kim et al recently reported one in five (19%) communitydwelling children and adolescents aged 6-17 years to have mental health problems [25]. The similarity of these two figures supports our finding that mental disorders are nearly four times more common in currently self-cutting adolescents than among other adolescents.…”
Section: Discussionsupporting
confidence: 90%
“…This may indicate underlying stress maybe caused by, or causing the parental divorce. Findings indicate that when examining mental health issues of children, parental stress, among other issues must be considered (34). The children's own separation is perhaps an indication of difficulties in intimate relationships, more common among children from divorced than intact families (35).…”
Section: Discussionmentioning
confidence: 99%
“…(i) one item on perceived quality of emotional relationship between the parents (response options: poor, fair, good, excellent) [6,9]; (ii) difficulty in psychosocial functioning. This was assessed by three items concerning difficulties being encountered as a result of various activities, viz: difficulty with studies (yes/no); difficulty relating with friends (yes/no); experiencing any other difficulties (yes/no); (iii) one item on perceived need for medical or psychological help (response options: no problem, need help only from friends, need medical/psychological help but not receiving it, need medical/psychological help and receiving it).…”
Section: Methodsmentioning
confidence: 99%
“…Of the parental factors, the consistent findings are that, poorer QOL was associated with parental low socio-economic status, low educational attainment, and divorce [3-5,7-10,15,44,45]. Of the socio-environmental factors, parental stress and the quality of emotional relationship between the parents were found to have long-term implications for the child's well-being [6,9,46,47]. Interestingly, children can reliably report on the quality of emotional relationship between their parents, while parents can predict children's response about parental relationship [46,48].…”
Section: Introductionmentioning
confidence: 99%